Curious enough to start up? How epistemic curiosity and entrepreneurial alertness influence entrepreneurship orientation and intention - Heinemann, Henrik; Mussel, Patrick; Schäpers, Philipp (Frontiers in Psychology, 2022)
Epistemic curiosity as the desire to acquire new knowledge and ideas is considered as an important attribute for successful entrepreneurs among practitioners, yet there is lacking empirical evidence of epistemic curiosity having an effect on entrepreneurial outcomes. This study aims to put a spotlight on epistemic curiosity as a predictor for entrepreneurial intentions and orientation. We found that epistemic curiosity has a stronger influence on entrepreneurial outcomes in comparison to the Big Five personality trait openness to experience, which is a widely used and conceptually related predictor for entrepreneurship. Furthermore, we found evidence for a mediating role of entrepreneurial alertness which gives further insights about how personality influences the ability to recognize business opportunities and leads to the formation of entrepreneurship orientation and intentions. Our findings contribute to the field of entrepreneurship research by emphasizing that epistemic curiosity may be one of the most important personality indicators for the emergence of entrepreneurial intentions and behavior.